Clinical Applications of Magnetoencephalography - Tobimatsu, Shozo; Kakigi, Ryusuke (Springer Japan : Imprint: Springer, 2016)
This book presents an overview of the recent advances in clinical applications of magnetoencephalography (MEG). With the expansion of MEG to neuroscience, its clinical applications have also been actively pursued. Featuring contributions from prominent experts in the fields, the book focuses on the current status of the application of MEG, not only to each nervous system but also to various diseases such as epilepsy, neurological disorders, and psychiatric disorders, while also examining the feasibility of using MEG for these diseases. Clinical Applications of Magnetoencephalography offers an indispensable resource for neurologists, neurosurgeons, pediatricians, and psychiatrists, as well as researchers in the field of neuroscience. .